Obstacles to Distance Learning During the Covid-19 Pandemic for Prospective Science Teacher Students - Riska Nabila; Nurlaila; Nining Purwati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Covid-19 virus outbreak has changed the learning process in higher education from face-to-face learning to distance learning online (on the network). Distance learning via online raises obstacles or challenges faced by both lecturers and students. This research aims to determine the obstacles to online learning during the Covid-19 pandemic among prospective science teacher students at Mataram State Islamic University. This type of research is descriptive qualitative research using Internet-based research methods through the distribution of Google forms. The research population was all Tadris IPA Biology students and there were 23 students as respondents. Research data analysis uses qualitative analysis techniques. From the research results, it was concluded that the obstacles faced by students include network disruption, limited and expensive internet quota, e-learning disruption, lack of lecturer explanations, an environment that disrupts focus on learning, and economic problems